Towards a Holarctic synthesis of peatland testate amoeba ecology: Development of a new continental-scale palaeohydrological transfer function for North America and comparison to European data. (1st December 2018) - Amesbury, Matthew J.; Booth, Robert K.; Roland, Thomas P.; Bunbury, Joan; Clifford, Michael J.; Charman, Dan J.; Elliot, Suzanne; Finkelstein, Sarah; Garneau, Michelle; Hughes, Paul D.M.; Lamarre, Alexandre; Loisel, Julie; et al.
Abstract: Fossil testate amoeba assemblages have been used to reconstruct peatland palaeohydrology for more than two decades. While transfer function training sets are typically of local-to regional-scale in extent, combining those data to cover broad ecohydrological gradients, from the regional-to continental- and hemispheric-scales, is useful to assess if ecological optima of species vary geographically and therefore may have also varied over time. Continental-scale transfer functions can also maximise modern analogue quality without losing reconstructive skill, providing the opportunity to contextualise understanding of purely statistical outputs with greater insight into the biogeography of organisms. Here, we compiled, at moderate taxonomic resolution, a dataset of nearly 2000 modern surface peatland testate amoeba samples from 137 peatlands throughout North America. We developed transfer functions using four model types, tested them statistically and applied them to independent palaeoenvironmental data. By subdividing the dataset into eco-regions, we examined biogeographical patterns of hydrological optima and species distribution across North America. We combined our new dataset with data from Europe to create a combined transfer function. The performance of our North-American transfer function was equivalent to published models and reconstructions were comparable to those developed using regional training sets. The new model can therefore be used as an effective tool to reconstruct peatland palaeohydrology throughout the North American continent. Some eco-regions exhibited lower taxonomic diversity and some key indicator taxa had restricted ranges. However, these patterns occurred against a background of general cosmopolitanism, at the moderate taxonomic resolution used. Likely biogeographical patterns at higher taxonomic resolution therefore do not affect transfer function performance. Output from the combined North American and European model suggested that any geographical limit of scale beyond which further compilation of peatland testate amoeba data would not be valid has not yet been reached, therefore advocating the potential for a Holarctic synthesis of peatland testate amoeba data. Extending data synthesis to the tropics and the Southern Hemisphere would be more challenging due to higher regional endemism in those areas. Highlights: Dataset of ca. 2000 North American peatland testate amoeba surface samples compiled. Palaeohydrological transfer functions tested statistically, applied to independent palaeo data. New model an effective tool for palaeohydrological reconstruction across North America. Biogeographical patterns occur at taxonomic resolution applied; taxa hydrological optima mostly robust across North America. Combined North American and European dataset illustrates potential for Holarctic synthesis.